The Implementation of HSK 汉语水平考试 Teaching Materials To Train Students’ Hsk 4 Vocabulary - Karina Fefi Laksana Sakti; Amira Eza Febrian Putri; Aiga Ventivani; Octi Rjeky Mardasari; Cicik Arista (Universitas Cokroaminoto Palopo, 2025)
This study aims to describe the process of implementing HSK 4 Preparation teaching materials 汉语水平考试 [Hànyǔ Shuǐpíng Jǎoshì sì jí], and students' responses to the implementation of HSK 4 Preparation teaching materials [Hànyǔ Shuǐpíng Jǎoshì sì jí]. This study uses a qualitative descriptive research method. The results of this study are that the process of implementing HSK 4 Preparation teaching materials ran smoothly, the classroom situation was very conducive and students were enthusiastic and eager to learn using HSK 4 Preparation digital teaching materials. Based on questionnaires and interviews, the implementation of HSK 4 Preparation digital teaching materials had a positive impact on students. Most students think that HSK 4 Preparation digital teaching materials make it easier for students to master HSK 4 vocabulary, increase motivation to learn HSK 4 vocabulary, the teaching materials are easy to access, and can be used for independent learning.